2014
DOI: 10.1159/000362982
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Modulates Dendritic Cell Function: Focus on Non-Migratory Effects <b><i>in Vitro</i></b> and <b><i>in Vivo</i></b>

Abstract: Dendritic cells (DCs) are the cutting edge in innate and adaptive immunity. The major functions of these antigen-presenting cells are the capture, endosomal processing and presentation of antigens, providing them an exclusive ability to provoke adaptive immune responses and to induce and control tolerance. Immature DCs capture and process antigens, migrate towards secondary lymphoid organs where they present antigens to naive T cells in a well-synchronized sequence of procedures referred to as maturation. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 92 publications
(144 reference statements)
0
29
0
Order By: Relevance
“…It is however very possible that the significant intracellular accumulation of this substance described by our data, may explain part of the surprising therapeutic efficacy of even low dosage levels in MS as compared to its formerly applied dosage in transplantation (Kappos et al, 2010). Therefore, by interpreting our findings in a positive direction, Fingolimod may affect immune cell-relevant intracellular targets, such as phospholipase A2 (PLA2) and protein phosphatase 2A (PP2A) (Payne et al, 2007;Saddoughi et al, 2013;Arlt et al, 2014). These results have to be further confirmed by an in vivo model, e.g.…”
Section: Discussionmentioning
confidence: 75%
“…It is however very possible that the significant intracellular accumulation of this substance described by our data, may explain part of the surprising therapeutic efficacy of even low dosage levels in MS as compared to its formerly applied dosage in transplantation (Kappos et al, 2010). Therefore, by interpreting our findings in a positive direction, Fingolimod may affect immune cell-relevant intracellular targets, such as phospholipase A2 (PLA2) and protein phosphatase 2A (PP2A) (Payne et al, 2007;Saddoughi et al, 2013;Arlt et al, 2014). These results have to be further confirmed by an in vivo model, e.g.…”
Section: Discussionmentioning
confidence: 75%
“…The application of different models of colitis (DSS versus 2,4,6-trinitrobenzene sulfonic acid (TNBS)), strongly support the conclusion that FTY720 regulates different aspects of lymphocyte biology (Degagne and Saba, 2014). Additionally, FTY720 has been implicated in the regulation of dendritic cell development and modulation of effector functions such as antigen processing, Th-priming and cytokine production (Arlt et al, 2014; Idzko et al, 2002; Muller et al, 2005; Radeke et al, 2005). Recently, it was shown that regulation of S1PR1 expression represents another mechanism of altering sphingolipid signaling in colitis.…”
Section: Bioactive Sphingolipid Signaling In Ulcerative Colitismentioning
confidence: 99%
“…However, during chronic or persistent or non-reactive TB, enhanced pulmonary titer of ceramide/sphingolipids in hitratho would oppose immune attack mechanisms and would promote bacterial persistency by their virtue of promote hypoxia. Other mechanisms, which could favor mycobacterial survival either separately or in concert, could include sphingolipid-driven polarization of effector T cells and M1 macrophages toward Treg (4648) and M2 macrophages (49, 50), which are refractory in nature and promote anti/sterile inflammatory response around granuloma. Under such cases, employing sphingolipids inhibitors in combination of TB drugs is believed to help in breaking mycobacterial persistency and ameliorating rifamycin resistance (5153), which is still a major challenge for preventing relapse.…”
Section: Clinical Perspectivesmentioning
confidence: 99%